CT-Guidance combined with fluoroscopy for tunnelled translumbar catheterization of inferior vena cava: a technical case report - Nik Rizal NY,; Shahrina MH,; Abdullah M,; Rozman Z,; Sobri M, (Department of Surgery, UKM Medical Centre, 2011)
Patients with end-stage renal disease typically require catheter hemodialysis during the time required for fistula or graft maturation or after other methods of hemodialysis are exhausted. When patients requiring indwelling catheters develop central venous occlusions, unconventional routes to the central veins are used. Translumbar catheterization of inferior vena cava is considered as one of the options for central venous access. We highlight a case of Translumbar central venous tunelled catheterization performed under Computed Tomography (CT) guidance combined with fluroscopy in a 40-year-old lady with end-stage renal failure.